Special Issue "Sports Science in Children" - Diogo Coutinho; Bruno Travassos; Sara Santos; Pedro Figueiredo; Adam Leigh Kelly (MDPI AG, 2024)
In recent times, research and technological advancements have opened an unprecedented window of opportunity for sports science to play a pivotal role in the holistic well-being of children [...]